A step-by-step intraoperative strategy during one-stage reconstruction of an acute electrical burn injury in the neck for superior surgical outcome in India: a case report - Mainak Mallik; Sanjay Kumar Giri; M. Vishnu Swaroop Reddy; Kallol Kumar Das Poddar (Journal of Trauma and Injury)
Electrical burn injuries can cause more damage than clinical evaluations initially suggest. The energy waves penetrate from the surface to the deepest layers of tissue, causing extensive harm at every level. The neck is a critical area, both functionally and aesthetically. We present a case involving a young male patient with a severe fourth-degree electrical burn on the neck, who underwent a single-stage debridement and reconstructive surgery. The pectoralis major myocutaneous flap is a versatile option for various head and neck reconstructions. However, if the donor site cannot be closed primarily and requires split-thickness skin grafting, it can result in unsightly scars and deformities. For large flap paddles, it is ideal to reconstruct the secondary defect with locoregional flaps. In this case, we successfully reconstructed the donor site's secondary defect using a contralateral internal mammary artery perforator flap, without resorting to any skin grafts. The early postoperative results demonstrated satisfactory cosmesis, patient satisfaction, and functional outcomes.